Political Life beyond the Biopolitical? - de Vries, Leonie Ansems (Theoria: A Journal of Social & Political Theory, 2013)
Michel Foucault's genealogy of the entry of life into politics provides an incisive account of the manner in which life came to be governed on the basis of its understood biological capacities and requirements. Foucault problematises biopolitics as a mode of governance through which life's potentialities are both produced and immobilised via the continuous (re)production of circulations, or the constitution of the milieu. The question is whether governance can be (dis)ordered such that this problem of biopolitical foreclosure is overcome. This problematique will be broached in this article by staging an encounter between Foucault's problematisation of biopolitical life and Gilles Deleuze and Félix Guattari's biophilosophy, which offers the promise of an ontological movement to think political life anew. Engaging Deleuze and Guattari's concept of the milieu, the article explores whether a shift of focus to an understanding of political life in terms of its potentialities of mobile and relational becoming within a wider play of forces can offer a viable strategy to counter the problematic foreclosure of politics to which Foucault draws attention.